Enhancing athletic performance and well-being: The role of RFID Technology in health monitoring and sports psychology - Yıldız Öztürk, Rabia; Pekgor, Metin; Algin, Aydolu; Toros, Turhan; Serin, Emre; Tek, Tolga; Ergun, Selcan (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study examined the integration of Radio-Frequency Identification (RFID) technology into sports psychology to enhance the monitoring and support of athletes’ physical and mental performance. The review focused specifically on technologies used in sport performance and sport psychology contexts. Two groups of technologies were considered: 1) Wearable sensors. 2) RFID-based systems. Through the use of RFID-enabled wearable sensors, athletes can be tracked non-intrusively, providing real-time data on physiological markers such as heart rate, skin temperature, and muscle activity, as well as psychological indicators like stress levels and emotional states. RFID technology enables the collection of data without direct contact, offering new possibilities for understanding the complex interactions between physical exertion and mental resilience. By combining RFID with the Internet of Things (IoT), this approach allows for continuous performance monitoring and personalized feedback, thereby helping athletes optimize their training and recovery strategies. This paper highlights the potential of RFID in sports psychology, underscoring its capability to improve athlete well-being and performance through innovative monitoring and tailored interventions.